The JAPAN-FORTA (Fit fOR The Aged) list: consensus validation of a clinical tool to improve drug therapy in older adults - Pazan, Farhad; Gercke, Yana; Weiß, Christel; Wehling, Martin; Akazawa, Hiroshi; Kojima, Taro; Kumaki, Ryota; Akishita, Masahiro; Takeya, Yasushi; Ohno, Yoshiyuki; Yamanaka, Takashi; Kozaki, Koichi; et al. (Archives of gerontology and geriatrics, 2020)
Purpose - Multimorbidity and subsequent polypharmacy are highly prevalent in older people. To improve inappropriate drug treatment, listing approaches such as the Beers or FORTA lists have been developed. Latter is the only clinically validated drug list issuing both positive (FORTA labels A, B) and negative (FORTA labels C, D) recommendations. Several country-specific FORTA lists have been developed to acknowledge national prescription habits, drug availabilities, and expert opinions. Here, this approach was applied to Japan. - Methods - 13 Japanese experts in geriatric pharmacotherapy participated as raters in a 2-step Delphi consensus validation of the FORTA list. The proposal of FORTA labels was based on the EURO-FORTA List and raters were asked to add, delete or re-evaluate medications, add relevant diagnoses and comments. - Results - The final JAPAN-FORTA list contains 210 items aligned to 24 main indication groups. 15 items were added to the proposal and the 71 items either not used/approved in Japan or not evaluated by any rater (oncological drugs) were removed. Excluding latter, the JAPAN-FORTA list differs from the EURO-FORTA list by 23 %. Removals mainly concerned psychotropic drugs. A maximum of one label was changed per indication. The majority (96.9 percent) of the proposed FORTA labels were confirmed, only 6 labels had to be changed. - Conclusion - The new JAPAN-FORTA list addresses the appropriateness of drug treatment in older people in Japan. This unique listing approach issuing both positive and negative medication recommendations has been shown to improve of drug therapy in older adults and its country-specific version is now available for Japan.